FORMULATION AND CHARACTERIZATION OF SELF EMULSIFYING DRUG DELIVERY SYSTEM OF SPIRONOLACTONE - Gupta, Ankur; Indurkhya, Arpna; Chaturvedi, S.C; Varma, Ajit (Asian Journal of Pharmaceutical Research and Development, 2019)
Spironolactone is aldosterone antagonist drug belonging to the category of potassium sparing diuretics administered orally that has absolute bioavailability of only 68% due to the poor aqueous solubility. The main aim of the present work was to develop a self emulsifying drug delivery system (SEDDS) to enhance the oral absorption of spironolactone. The solubility of spironolactone in various oils, surfactants, and co surfactants was determined. Pseudo ternary phase diagrams were constructed using castor oil, Tween 80, and polyethylene glycol 400, and distilled water to identify the efficient self-micro emulsion region. Prepared self emulsifying drug delivery system was further evaluated for its emulsification time, drug content, optical clarity, droplet size, zeta potential, in vitro drug release. The results showed that 96.16% drug was released from the SEDDS formulation in 3 hrs. This demonstrated an enhancement in the drug release and thereby, absorption of the drug through the membrane, this was significantly higher than that of the plain drug suspension. Thus, the above findings support that the utility of SEDDS to enhance solubility and dissolution of poorly water soluble compounds which may result in improved Therapeutic performance.